Understanding the overlap and differences in terms describing patterns of maladaptive avoidance and intolerance of negative emotional states. (1st May 2020) - Juarascio, Adrienne; Manasse, Stephanie; Clark, Kelsey E.; Schaumberg, Katherine; Kerrigan, Stephanie; Goldstein, Stephanie P.; Evans, Brittney C.; Wyckoff, Emily; Murray, Helen B.; Felonis, Christina R.; Forman, Evan
Highlights: Many extant terms describe avoidance/intolerance of aversive internal experiences. Substantial recurring content and similar wording across questionnaires. Many measures assess psychological view of non-acceptance towards negative emotions. Some terms (e.g., distress intolerance & emotion dysregulation) not truly unique. Moderate-to-large positive correlations between most avoidance/intolerance measures. Abstract: Maladaptive avoidance/intolerance of negative emotional states has been widely shown to contribute to negative outcomes. Growing interest in this construct has led to the use of multiple terms (e.g., emotion dysregulation, distress intolerance, experiential avoidance, anxiety sensitivity, negative urgency) to describe such individual differences, each with their own measurement tools. However, to date, the degree to which these terms reflect truly unique attributes is understudied. The aim of the current manuscript is to review five of the most common terms (and associated measurement tools) used to describe these patterns of avoidance/intolerance of negative emotional states to better understand areas of overlap and key differences. We used qualitative content analysis and examined correlations between measures across 114 datasets from published manuscripts (i.e., Difficulties in Emotion Regulation Scale, Distress Tolerance Scale, Acceptance and Action Questionnaire, Anxiety Sensitivity Index, UPPS Impulsive Behavior Scale–Negative Urgency Subscale; N = 28, 648 administrations). Our review suggests that measurement tools for existing terms demonstrate considerable qualitative overlap and moderate-to-large positive correlations ( r = 0.24–0.67). Failures to emphasize the unique features associated with each term in existing measures may have minimized the field's ability to evaluate distinct facets of avoidance/intolerance of negative emotional states and to determine whether these facets differentially predict outcomes. Graphical abstract: Image, graphical abstract